Peningkatan Niat dan Motivasi Berwirausaha: Peran Pendidikan Kewirausahaan pada Mahasiswa - Bella Ananda Chairunnisa (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Entrepreneurship is one of many sectors that supports economic growth in Indonesia. Indonesian mostly work as entrepreneurs, so entrepreneurship is one of economic growth’s pillars in Indonesia. Entrepreneurship can increase financial independence for those who do it. Work flexibility makes entrepreneurship an option that is in demand by many people, including students. However, interest and motivation in entrepreneurship need to be fostered, one of which is through entrepreneurship education. Using respondents from students of the Universitas Muhammadiyah Surakarta, this study tries to test the effect of entrepreneurship education on interest and motivation to become entrepreneurs. This study operates Smart Partial Least Squares (SPLS) to test the relationship between variables. The findings in this study confirm that entrepreneurship education can increase interest and motivation to become entrepreneurs, especially among students.